EVALUATING THE PERFORMANCE OF INSTANCES WITH DIFFERENT DISKS AND REGIONS IN MICROSOFT AZURE - Bezerra, Wagner; Universidade Federal do Ceará (2024)
The growing use of the internet brought the need for increasinglyrobust systems to support the number of userswho access them. The cloud computing paradigm came tosupply this need through infrastructure and complete computersystems, easily accessible to the user. In this work, anevaluation of the Microsoft Azure platform for cloud computingis performed. The IaaS model is used to carry out series of tests with the referred platform in order to verifythe performance of different configurations of linux virtualmachine instances. The performance of the disk options offeredfor virtual machines on the platform was observed,in instances with similar configurations. There is also aninfluence that the location of the instances has on their performance.Finally, it is possible to conclude that the performanceof the disks is not much different for data of size10 GB. It is also evident that the location of the instancesaffects CPU performance and network capacity.